The Alabama Human Life Protection Act: criticità giuridiche, contraddizioni assiologiche e dinamiche politiche evolutive (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Oggetto del presente contributo e metodologia di ricerca - 2. Analisi giuridica e rilievi critici - 3. Il paradigma morale interno - 4. La dinamica evolutiva - 5. Conclusioni.The Alabama Human Life Protection Act: juridical criticisms, moral contradictions and policy implicationsABSTRACT: The paper aims at analyzing and highlighting potential juridical criticism of the recent abortion law referred to as The Alabama Human Life Protection Act and verifying if the positive judgments, expressed by the international pro-life movement, and the potential legal, social and policy developments, triggered by this legislation, are consistent with the moral principles of the movement itself.
Keywords: Diritto ecclesiastico comparato e straniero